USING MODERN PEDAGOGICAL METHODS TO ASSESS STUDENTS' PHYSICAL ABILITIES - Nazarov Nursultan Safarbayevich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the application of modern pedagogical methods in assessing students' physical abilities. It emphasizes the importance of accurate and effective evaluation techniques to monitor development, provide feedback, and guide individualized instruction. The paper discusses various contemporary approaches, including performance-based assessments, technology-assisted evaluations, and interactive testing methods, which aim to enhance objectivity, student engagement, and overall learning outcomes. The study concludes that employing modern pedagogical methods in physical ability assessment improves the quality of education, supports personal growth, and fosters a lifelong interest in physical fitness.